An Al-Jazeera Effect in the USA? A Review of the Evidence - Samuel-Azran, Tal (Global Media Journal - German Edition, 2017)
Some scholars argue that following 9/11, Al-Jazeera has promoted an Arab perspective of events in the US by exporting its news materials to the US news market. The study examines the validity of this argument through a review of the literature on the issue during three successive periods of US-Al-Jazeera interactions: (a) Al-Jazeera Arabic’s representation in US mainstream media following 9/11, specifically during the wars in Afghanistan and Iraq; (b) Al-Jazeera English television channel’s attempts to enter the US market since 2006; and (c) the reception of Al-Jazeera America in the US, where the paper also adds an original analysis of Al-Jazeera America’s Twitter followers’ profiles. Together, these analyses provide strong counterevidence to the argument that Al-Jazeera was able to promote an Arab perspective of events in the US.